Depression symptoms and recurrent aphthous stomatitis—Evidence from a population‐based study in Indonesia. (21st February 2020) - Hariyani, Ninuk; Bramantoro, Taufan; Nair, Rahul; Singh, Ankur; Sengupta, Kaushik
Abstract: Objectives: This study aims to report the prevalence and distribution of recurrent aphthous stomatitis (RAS) among Indonesian adults and to test the relationship between symptom of depression and RAS. Methods: Data from the 2007 Indonesia Family Life Survey (IFLS 2007) were analysed to assess the association between symptom of depression and RAS. The prevalence of RAS in the previous month was self‐reported. Symptom of depression was measured using the 10‐item Center for Epidemiologic Studies Depression (CES‐D) scale. The distribution of RAS according to age, sex and level of stress was also presented in the bivariate analysis. Multivariable logistic regression models were fitted to test associations between symptom of depression and RAS, controlling for age, sex and the stress level. Results: The previous month prevalence of RAS in Indonesian population was 12%. The adjusted odds ratios (ORs) from the logistic regression models indicate that, for each unit increase in the CES‐D depression score (range: 0–30), there was a 9% increase in the odds of having RAS (OR: 1.09, 95%CI: 1.08–1.10). Being older and being male was related with lower prevalence of RAS. Conclusions: A higher score of depression was related to a higher prevalence of RAS. This association was persistent even after controlling for age, sex and the level of stress.